12 ÷ 3 × ( -8 + ( sqr( -4 ) - -6 ) + 2 ) explain?
Answers
Answered by
1
hope it helps.....
If u find it helpful...then plz mark it as the brainiest
Attachments:
![](https://hi-static.z-dn.net/files/d6b/b7d65d74eb26eb82306d2b7c22d44afa.jpg)
Answered by
0
Answer:
96
Step-by-step explanation:
12÷ 3 × ( -8 +( sqr(-4) - -6) +2) as per BDMAS rule
= 13 ÷ 3 × ( -8 +( -4 ×-4) +6) +2) first bracket open
= 4 × ( -8 + (16 + 6) + 2) then Divition then Multify
= 6 ×16
=96
Note : In this sum more brackets so Carefully open one by one
Similar questions